Study Of Performance Comparison of Sharia Shares In Indonesia And Malaysia: Sharpe, Treynor and Jensen Models - Utami, Yuni; Prasetya, Victor; Riyadi, Ragil Anwar (Riviera Publishing, 2022)
This study aims to analyze the differences in the performance of Islamic mutual funds using the Sharpe, Trenor and Jensen models on stock types of Islamic mutual funds in Indonesia and Malaysia for the 2017-2018 period. This research is descriptive with a quantitative approach. The sample in this study is sharia equity mutual funds in Indonesia and Malaysia in the 2017 - 2018 period. The data collection techniques used are secondary data, with analysis techniques by measuring performance with the Sharpe Trenor and Jensen models, and comparison with the average difference test technique.-average. Based on the results of the analysis of the two different tests on average, the results of differences in the performance of shariah mutual funds in Indonesia and Malaysia using the Sharpe, Trenor and Jensen models each have a significance value of 0.001 with the Sharpe model, 0.041 with the Trenor model and 0.049 with the Jansen model. This shows the level of difference in the performance of sharia mutual funds types of shares in Indonesia and Malaysia for the 2017-2018 period. And from the test results that the three methods used, the accuracy of the Sharpe model is better than the Trenor model and Jansen model.